Darier's disease: a focal abnormality of cell adhesion. - Burge, S; Millard, P; Wojnarowska, F; Ryan, T (1990)
Cell adhesion in clinically normal and involved skin in Darier's disease has been investigated using a suction blister technique. We have been unable to detect a subclinical abnormality in cell adhesion which could predispose to the development of acantholytic papules. There may be synthesis of functionally deficient desmosomes, increased breakdown of desmosomes or abnormalities in other adhesion proteins on the surface of the keratinocyte in Darier's disease, but the abnormality in adhesion is focal and restricted to the clinically and histologically abnormal papules.